FBG-Based Temperature and Fire Sensors for Use in Industrial Microwave Ovens - Yüksel Aldoğan, Kıvılcım; Yuksel, K.; Merdin, O. D.; Kinet, D.; Merdin, M.; Guyot, C.; Caucheteur, C. (SPIE, 2025)
Industrial microwave-heating systems play a crucial role in sectors such as food processing and materials manufacturing, where precise temperature control and safety are paramount. However, traditional systems often face challenges like uneven heat distribution and elevated fire risks due to the inherent characteristics of microwave heating. This study introduces a fiber-optic sensor-based monitoring system designed to address these critical issues. The system features an advanced fiber-optic sensor capable of 2D temperature distribution monitoring and a specialized fire detection mechanism, both aimed at significantly reducing risks and improving the heating process. Experimental results demonstrate the potential for transformative advancements in industrial heating technologies, paving the way for enhanced process efficiency and safety.
Keywords: Fiber Bragg Grating; Fire; Microwave Oven; Monitoring; Optical Fiber; Sensor; Temperature